Sociodemographic profile of referred obstetric women - Monika; Jain, Aditi; Verma, Krupa; Hooja, Nupur; Yadav, Shivangi; Bhagat, Saumya (International Journal Of Community Medicine And Public Health, 2025)
Background: Emergency obstetric care is an indicator of the health care services. Referral services play an important role in health management. Socio-demographic profile of the patients affect their health seeking behaviour. Methods: 220 referred women admitted in the hospital with more than 20 weeks pregnancy were evaluated. Socio-demographic details were noted and analysed. Results: There was a high percentage of referred women in >30 years. 74.09% had primary education or less, most belonged to the lower middle class or less and 64.55 % of women were from urban and urban slum area. Conclusions: The low educational level of women and poor socio-economic status play a key role in delay in the utilization of maternal health services. These women sought medical advice only when emergency arose and a high percentage of them had to be referred to higher centre. Focus on these women would improve their health seeking behaviour.